Keratinocytes oxidative damage mechanisms related to airbone particle matter exposure - Romani, Arianna (2017)
Epidemiological evidences have correlated airbone particulate matter (PM) to adverse health effects, mainly linking to pulmonary and cardiovascular disease. Nevertheless, only recently, some studies reported detrimental effects of PM on other organs such as skin. In a recent work, we have reported increased oxidative and inflammatory responses in Reconstituted Human Epidermis (RHE) exposed to ambient particles (CAPs) and we also demonstrated the ability of CAPs to penetrate the skin tissue.The present study was aimed to better understand the cellular mechanisms beyond the oxidative changes induced by CAPs (5-10-25. μg/mL) in human immortalized keratinocytes (HaCaT).After 24. h of treatment, CAPs were able to enter the cells leading to a decrease in viability, increased levels of 4-hydroxinonenal products (4-HNE) and IL-1α release. Overall these data, suggest lipid and protein oxidative damage, as well as an increase of inflammatory response after being challenged with CAPs. In addition, 3. h after CAPs exposure we found a significant increase in NF-kB and Nrf2 translocation into the nucleus. In contrast, no differences in gene expression and enzymatic activity of Nrf2 target genes were detected. This last finding could be explained by the ability of CAPs to possibly alter the binding of Nrf2 to the ARE DNA sequence.